2023
DOI: 10.3390/ijms24021547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Exposure on Staphylococcus epidermidis Responsible for Catheter-Related Bacteremia

Abstract: Coagulase-negative staphylococci (CoNS) and especially Staphylococcus epidermidis are responsible for health care infections, notably in the presence of foreign material (e.g., venous or central-line catheters). Catheter-related bacteremia (CRB) increases health care costs and mortality. The aim of our study was to evaluate the impact of 15 days of antibiotic exposure (ceftobiprole, daptomycin, linezolid and vancomycin) at sub-inhibitory concentration on the resistance, fitness and genome evolution of 36 clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…For example, we excluded CDC commensal microorganisms from the HOB definition to be consistent with a recently published paper; 8 however, commensals can be true pathogens depending on the number, proximity, and clinical interpretation of positive blood cultures. 21,22 Our data support and update prior reports on the burden of HOB in hospitalized patients. The ∼30% mortality rate of HOB in our study is generally comparable to HOB mortality rates reported in other US hospitals 23,24 and in Denmark, 25 and the mortality rate of 35.3% in patients with an ICU encounter is similar to the 36.6% reported in ICU admissions in France.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, we excluded CDC commensal microorganisms from the HOB definition to be consistent with a recently published paper; 8 however, commensals can be true pathogens depending on the number, proximity, and clinical interpretation of positive blood cultures. 21,22 Our data support and update prior reports on the burden of HOB in hospitalized patients. The ∼30% mortality rate of HOB in our study is generally comparable to HOB mortality rates reported in other US hospitals 23,24 and in Denmark, 25 and the mortality rate of 35.3% in patients with an ICU encounter is similar to the 36.6% reported in ICU admissions in France.…”
Section: Discussionsupporting
confidence: 87%
“…For example, we excluded CDC commensal microorganisms from the HOB definition to be consistent with a recently published paper; 8 however, commensals can be true pathogens depending on the number, proximity, and clinical interpretation of positive blood cultures. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…Whole Genome Sequencing (WGS) was carried out using Illumina MiSeq Sequencing system (Illumina, San Diego, CA, USA). Illumina library preparation was constructed using 250 ng of the extracted DNA following the Nextera XT DNA Prep Kit library paired-end protocol (paired-end read libraries, Illumina) and sequenced in a 39 h run providing 2 × 250 bp reads as previously described [38]. Quality control of the reads was performed directly on MiSeq output reads using FastQC software (v.0.11.7).…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…However, based on reports that have included species identification, one can assume that the vast majority of non-specified coagulase-negative staphylococci infections are due to S. epidermidis . In addition, S. epidermidis produces several factors used to colonise tissues or artificial surfaces, such as catheters [ 3 ]. Patients, especially those with an immunocompromised status, are susceptible to nosocomial infections through the use of devices and invasive procedures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%